Integrated Network Pharmacology Analysis and Experimental Validation to Reveal the Mechanism of Anti-Insulin Resistance Effects of Moringa oleifera Seeds - Huang Q; Liu R; Liu J; Huang Q; Liu S; Jiang Y (Dove Medical Press, 2020)
Qiong Huang,1– 3,* Rong Liu,1– 3,* Jing Liu,1– 3 Qi Huang,1– 3 Shao Liu,1– 3 Yueping Jiang1– 3 1Department of Pharmacy, Xiangya Hospital, Central South University, Changsha 410008, People’s Republic of China; 2Institute of Hospital Pharmacy, Central South University, Changsha 410008, People’s Republic of China; 3Institute for Rational and Safe Medication Practices, National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shao Liu; Yueping JiangDepartment of Pharmacy, Xiangya Hospital, Central South University, 87 Xiangya Road, Changsha, Hunan 4100080, People’s Republic of ChinaEmail liushao999@csu.edu.cn; jiangyueping@126.comBackground and Purpose: Insulin resistance (IR) is one of the factors that results in metabolic syndrome, type 2 diabetes mellitus and different aspects of cardiovascular diseases. Moringa oleifera seeds (MOS), traditionally used as an antidiabetic food and traditional medicine in tropical Asia and Africa, have exhibited potential effects in improving IR. To systematically explore the pharmacological mechanism of the anti-IR effects of MOS, we adopted a network pharmacology approach at the molecular level.Methods: By incorporating compound screening and target prediction, a feasible compound-target-pathway network pharmacology model was established to systematically predict the potential active components and mechanisms of the anti-IR effects of MOS. Biological methods were then used to verify the results of the network pharmacology analysis.Results: Our comprehensive systematic approach successfully identified 32 bioactive compounds in MOS and 44 potential targets of these compounds related to IR, as well as 37 potential pathways related to IR. Moreover, the network pharmacology analysis revealed that glycosidic isothiocyanates and glycosidic benzylamines were the major active components that improved IR by acting on key targets, such as SRC, PTPN1, and CASP3, which were involved in inflammatory responses and insulin-related pathways. Further biological research demonstrated that the anti-IR effects of MOS were mediated by increasing glucose uptake and modulating the expression of SRC and PTPN1.Conclusion: Our study successfully predicts the active ingredients and potential targets of MOS for improving IR and helps to illustrate mechanism of action at a systemic level. This study not only provides new insights into the chemical basis and pharmacology of MOS but also demonstrates a feasible method for discovering potential drugs from traditional medicines.Keywords: network pharmacology, Moringa oleifera seeds, IR, active components, action mechanism